Regulatory and financial burdens of EU legislation in four Member States – a comparative study. Vol. 3: Burdens arising from the transparency register of the Anti-Money Laundering Directive - Lukas Harta; Marion Jousseaume; Bert Van Roosebeke; Andrea De Petris; Jan Tiessen; Lorenz Löffler; Paul Braunsdorf; Pia Czarnetzki; Jessica Catalano; Louis Colnot; Matteo Pedralli (Foundation for Family Businesses, 2023)
The research project on the costs of bureaucracy extends to four volumes on four different regulations. Part three is dedicated to the transparency register. Here the information required in four member countries of the EU was examined along with the economic costs to companies that result in practice. – – Das Forschungsprojekt "Bürokratiekosten" erstreckt sich über vier Bände zu vier verschiedenen Regulierungen. Teil 3 widmet sich dem Transparenzregister. Hier wurden die erforderlichen Angaben in vier Mitgliedsländern der EU untersucht und die ökonomischen Kosten in der Unternehmenspraxis.
Keywords: 330